Vertical Integration and Technological Innovation - Armour, Henry Ogden; Teece, David J. (The Review of Economics and Statistics, 1980)
The authors find that a significant relationship exists between vertical integration and expenditures for basic and applied research for the US petroleum industry, 1954-1975. They advance several hypotheses consistent with this finding, and conclude that organizational structure influences expenditures on research in the modern business enterprise.